Rhodium-Catalyzed, Phosphorus(III)-Directed Hydroarylation of Internal Alkynes: Facile and Efficient Access to New Phosphine Ligands - Luo, Huanhuan; Wang, Dawei; Wang, Minyan; Shi, Zhuangzhi (Synlett, 2021)
Organophosphines are an important class of ligands widely used in organic chemistry. Although great progress has recently been made in the rapid construction of new phosphines through Rh- or Ru-catalyzed C–H bond functionalizations, synthetic access to more diverse phosphines remains a challenge. We describe an efficient process for the rhodium-catalyzed phosphorus(III)-directed hydroarylation of internal alkynes to generate various alkenylated and 2′,6′-dialkenylated biarylphosphines with high selectivity. A range of diverse alkynes and phosphines were effectively prepared with broad functional-group compatibility under the optimized conditions. In addition, the developed protocol can be extended to modify chiral phosphine ligands, providing enantioenriched alkenylated phosphines without erosion of the enantiomeric excess.
Keywords: rhodium catalysis; hydroarylation; alkynes; phosphines; C–H activation; directing group